2020
DOI: 10.21037/atm.2019.12.155
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 prevents early diabetic retinopathy via reducing retinal ganglion cell layer and inner nuclear layer cell apoptosis in db/db mice

Abstract: Background: Diabetic retinopathy (DR), a diabetic vascular complication, is prone to developing into blindness. Ginsenoside Rg1 (GRg1), a major saponin in ginseng, exerts high anti-apoptotic activity.Methods: This study aimed to explore the protective effects of GRg1 against diabetes-induced retinal damage. Measurements of blood glucose, blood lipids and vascular permeability were performed, as well as assessments of pathological changes, and the retinal thickness of each layer. Retinal cell apoptosis related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
2
12
0
Order By: Relevance
“…Regarding the gene expression level, Rg1 increased SIRT3 but decreased VEGF in rat retinal tissue and inhibited HRECs proliferation, migration and angiogenesis. It is consistent with the finding by Gao et al [ 17 ] that Rg1 can prevent DR by reducing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the gene expression level, Rg1 increased SIRT3 but decreased VEGF in rat retinal tissue and inhibited HRECs proliferation, migration and angiogenesis. It is consistent with the finding by Gao et al [ 17 ] that Rg1 can prevent DR by reducing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Rg1 can improve endoplasmic reticulum stress-induced apoptosis in diabetic cardiomyopathy induced by streptozotocin (STZ) [ 16 ]. Rg1 prevents retinal damage by inhibiting retinal cell apoptosis [ 17 ]. Moreover, experimental studies have shown that ginsenoside Rg1 plays a role in promoting vascular regeneration and enhancing endothelial progenitor cell angiogenesis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This retinal thinning correlated with the increased apoptosis observed in each of the retinal models. 15 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Mice fed a high-fat diet exhibit impairments in a-wave, b-wave, and oscillatory potentials (OPs) on ERG testing, suggesting neuronal injury, though inner retinal thinning was not noted [33][34][35]. On the other hand, the db/db leptin-receptor-deficient mouse manifests both retinal functional deficits on ERG as well as RGC loss as early as 8 weeks of age [36][37][38]. Finally, diabetic retinal neurodegeneration has been documented, though less wellstudied, in other animal models.…”
Section: Animal Models Of Early Diabetic Retinal Neurodegenerationmentioning
confidence: 99%